Framing the bride : globalizing beauty and romance in Taiwan's bridal industry - Adrian, Bonnie, 1970- (University of California Press, 2003)
With a wedding impending, the Taiwanese bride-to-be turns to bridal photographers, makeup artists, and hair stylists to transform her image beyond recognition. They give her fairer skin, eyes like a Western baby doll, and gowns inspired by sources from Victorian England to MTV.